Reimagining Leslie Cheung through Hanyuan Bookstore: the posthumous personalities of the queer Hong Kong celebrity. Issue 4 (2nd October 2022) - Bukowski, Ana Howe; Lv, Junyi
ABSTRACT: This paper considers the posthumous celebrity of Hong Kong singer and actor Leslie Cheung, taking into account his amplified profile among fan communities following his 2003 suicide. Through a site analysis of the now-closed Hanyuan Bookstore in Shanghai, a major site of pilgrimage for his fans, our work is structured through an analysis of the bookshop space as well as a reading of the compendium of handwritten fan letters left behind and addressed to Cheung beyond the grave. To this end, we argue for the necessary queerness of Cheung's status as celebrity. This queerness is not only the product of his sexual identity and his relationship with Daffy Tong, but due to the spatio-temporal orientation of Hanyuan. With Cheung maintaining a posthumous presence in the space, Hanyuan embodies and instantiates multiple spatio-temporal registers and offers a space for affective re-orientation in face of the everyday, creating a commensurate site of proximity between living fan and deceased star. With Hanyuan standing as a unique site of pilgrimage linking past and future and enhancing already-held parasocial relations, this paper equally considers the geographic particularities of Cheung's posthumous celebrity status within a more complex field of contemporary Chinese-speaking popular culture.